Situation Report: Bulgaria, 13 November 1968 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Decree on Overall Application of the New Economic System Zhivkov Addresses Polish Party Congress Additional Emphasis on Political Qualifications of Specialists Bulgarian-Turkish Relations Norwegian Trade Delegation in Bulgaria